The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.neulet.2008.05.112
|View full text |Cite
|
Sign up to set email alerts
|

Statin inhibits kainic acid-induced seizure and associated inflammation and hippocampal cell death

Abstract: Statins are inhibitors of HMG-CoA reductase that have been recently recognized as antiinflammatory and neuroprotective drugs. Herein, we investigated anti-excitotoxic and anti-seizure effects of statins by using kainic acid (KA)-rat seizure model, an animal model for temporal lobe epilepsy and excitotoxic neurodegeneration. We observed that pretreatment with Lipitor (atorvastatin) effeiciently reduced KA-induced seizure activities, hippocampal neuron death, monocyte infiltration and proinflammatory gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
109
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 43 publications
(64 reference statements)
13
109
0
1
Order By: Relevance
“…3. Discussion Previous studies have suggested that the statin class of cholesterol synthesis inhibitors are capable of protecting against hippocampal injury in models of seizure--induced neuronal death (He et al, 2006, Lee et al, 2008, Piermartiri et al, 2009, Rangel et al, 2005and Xie et al, 2011. Statin treatment has been shown to reduce cell death in the hippocampus in mice with quinolinic acid--induced seizures and in rats with pilocarpine and KA--induced seizures.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…3. Discussion Previous studies have suggested that the statin class of cholesterol synthesis inhibitors are capable of protecting against hippocampal injury in models of seizure--induced neuronal death (He et al, 2006, Lee et al, 2008, Piermartiri et al, 2009, Rangel et al, 2005and Xie et al, 2011. Statin treatment has been shown to reduce cell death in the hippocampus in mice with quinolinic acid--induced seizures and in rats with pilocarpine and KA--induced seizures.…”
Section: Introductionmentioning
confidence: 83%
“…Lovastatin treatment does not prevent hippocampal damage caused by intra--amygdala KA--induced status epilepticus Statins have been reported to have potent neuroprotective effects against seizure--induced neuronal death in rats (Lee et al, 2008, Ohyama et al, 2006and Rangel et al, 2005. To test if lovastatin treatment has such an effect in the present model, mice were treated for three consecutive days with lovastatin using a dose previously shown to lower brain cholesterol in animal models (Lee et al, 2008). On the fourth day, mice received lovastatin before and after being subjected to KA--induced status epilepticus, and then received lovastatin again on the two subsequent days.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations